Fire characteristics of rescue station inside railway tunnel with semi-transverse ventilation. (April 2020) - Zhou, Yuanlong; Bi, Haiquan; Wang, Honglin; Lei, Bo
Highlights: We study fire characteristics of rescue stations with semi-transverse ventilation. The smoke is controlled within the nearest two shafts under exhaust velocity of 3 m/s. Fire source position affects smoke temperature distribution at the top of rescue station. The piston wind influences the visibility distribution within the first 60 s. Smoke stratification is obvious in the semi-transverse ventilation mode. Abstract: Rescue stations are essential in long railway tunnels to provide a safe, smoke-free refuge for evacuated passengers in the event of a fire. The fire characteristics of rescue stations with semi-transverse ventilation are significantly different from those with longitudinal ventilation. In this work, the fire characteristics of a rescue station with semi-transverse ventilation are studied using numerical simulations. The numerical method is verified using 1:20 scale model experiment. The dependencies of the temperature and visibility on the smoke exhaust velocity, fire source position, and piston wind are discussed in detail. The results demonstrate that the smoke temperature distribution at the top of rescue station is related to the fire source location. When the fire source is under the shaft, the maximum smoke temperature at the top of the rescue station decreases with an increase in the smoke exhaust velocity; when the fire source is in the middle of two shafts, the maximum smoke temperature is independent of the smoke exhaust velocity. When the smoke exhaust velocity is 3 m/s, all of the smoke is controlled between vertical shafts no. 2 and no. 4. This conclusion is significantly different from that of longitudinal ventilation. On the evacuation platform of the rescue station, the smoke exhaust velocity has little influence on the smoke temperature distribution, and the temperature at a height of 2 m can meet the specification requirements of lower than 60 °C for a 20 MW fire source. Moreover, the piston wind has an influence on the visibility of the evacuation platform, which is another obvious fire characteristic for semi-transverse ventilation.